Adoption and Effectiveness of Automated Dispensing Cabinets in Reducing Medication Errors in Saudi Tertiary Care Centers (The Review of Diabetic Studies, 2025)
Objective: This study aimed to evaluate the adoption, utilization, and perceived effectiveness of automated dispensing cabinets (ADCs) in tertiary care hospitals in Saudi Arabia and to assess their impact on medication safety and workflow efficiency.Methods: A cross-sectional, mixed-methods design was employed, including 400 healthcare professionals (nurses, pharmacists, and pharmacy technicians) across medical, surgical, and critical care units. Quantitative data included ADC utilization metrics and retrospective analysis of medication error reports before and after ADC implementation. Qualitative data were collected through open-ended survey items to identify facilitators and challenges associated with ADC use. Descriptive and inferential statistics were applied, and thematic analysis was conducted for qualitative responses.Results: ADCs were widely adopted and frequently utilized, with users accessing systems an average of 18 times per shift. Healthcare professionals reported overwhelmingly positive perceptions regarding ADC effectiveness, usability, and workflow integration. Implementation of ADCs was associated with a substantial reduction in overall medication errors (–25.3%), particularly in dispensing and preparation stages. Qualitative findings highlighted that structured training, organizational support, and integration with electronic systems were key facilitators, while minor workflow adjustments and technical challenges were manageable.Conclusion: ADCs are effective, well-accepted, and integral to improving medication safety and workflow efficiency in tertiary care settings. Their success depends on comprehensive training, strong institutional support, and integration with electronic medication management systems. Complementary interventions are recommended to address administration-stage errors, and future research should explore long-term sustainability and integration with emerging technologies.